2016
DOI: 10.1111/1756-185x.12928
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of ultrasonographic features of gout in intercritical and chronic phase

Abstract: MSUS is useful for diagnosis of gout in intercritical or chronic stages, especially in patients with persistently high SUA level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The most common joint involved was ankle, followed by the metatarsophalangeal joints. Previous studies also have shown a male preponderance with metatarsophalangeal joints, knee and ankle being the most common sites of involvement (15). Tubercular arthritis is among the commonest causes of infectious arthritis in endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…The most common joint involved was ankle, followed by the metatarsophalangeal joints. Previous studies also have shown a male preponderance with metatarsophalangeal joints, knee and ankle being the most common sites of involvement (15). Tubercular arthritis is among the commonest causes of infectious arthritis in endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also supported high specificity (90% range) for DCS [55][56][57]. However, in patients with gout for less than 2 years, sensitivity (50%) is lower than for patients with established disease ≥ 2 years duration (63%).…”
Section: Ultrasound Evaluation Of Crystalline Arthropathymentioning
confidence: 90%
“…There are many practical advantages in the use of ultrasound for the evaluation of gout compared to the previously mentioned imaging modalities. These include ultrasound's ready availability at the bedside, low operational costs and time, real-time information for clinicians, and the ability to perform a rapid examination of multiple locations [22][23][24]. The increase of skilled clinician sonographers and of ultrasound equipment makes POCUS an ideal bedside tool for the assessment of the patient with crystal arthropathy.…”
Section: Ultrasound Features Of Goutmentioning
confidence: 99%